The potential role of Red Tilapia (Oreochromis niloticus) scales: allergic reaction test in mice - Abdul Rahman, Suzanah; Zambry, Husna; Basha, Sadak; Kamarzaman, Saheera; Khan Chowdhury, Ahmed Jalal (Journal of Applied Pharmaceutical Science (http://www.japsonline.com), 2013)
Red tilapia (Oreochromis niloticus) is one of aquaculture’s most adaptive species. It is abundantly found in the wild and known to be cultured in several parts of the world. It is mainly a freshwater fish, inhabiting shallow streams, ponds, rivers and lakes but less commonly found living in brackish water. The concept of ‘waste to wealth’ has been applied widely as an alternative to waste reduction and environmental conservation. Based on these perspectives, the present study was conducted to assess possible medicinal and pharmaceutical values of the tilapia. The mice model of delayed-contact hypersensitivity test, the mice ear swelling test (MEST), was chosen for this study due to its ability to predict contact sensitization with less cost and time consumed. Four female BALB/c mice were tested in each group which included controls. Three different doses of scales powder at 500, 1000, and 2000 mg/kg in an acetone and olive oil (AOO) solution were formulated and applied to shaved dorsal trunk of the mice at induction phase, and to both sides of each ear of the mice at elicitation phase. From the observations made throughout the study period, neither erythema nor oedema was formed on the skin of mice treated with scales powder in AOO solution. Mice ear thickness increase showed percentage ear swelling of no more than 20%. Thus, the finding of this study showed that the scales of red tilapia fish did not induce allergic sensitization and could have an application in medicinal and pharmaceutical industries.